The Effect of Service Quality and Product Quality on Consumer Repurchase Intention with Satisfaction as A Mediating Variable at Putri Ayu's Weaving in Gianyar Regency - Ni Komang Dewik Ariani; I Gusti Ayu Wimba; Mirah Ayu Putri Trarintya (Management and Applied Social Studies Review, 2023)
Purpose – The aim of this study is to examine the effect of service quality and product quality on customer return through satisfaction at Putri Ayu Weaving in Gianyar Regency. Methodology – In this study, a survey questionnaire was administered to 85 participants, and the data were analysed using SEM-PLS.. Findings – show that satisfaction plays an important role in purchase intention, where physical evidence is the main factor of service quality and design is the main factor of product quality. It has also been shown that satisfaction is often influenced by price. The results also confirm that service quality has a positive and positive effect on customer satisfaction, product quality has a positive and positive effect on customer satisfaction, service quality has a positive and positive effect on repeat intention, and product quality has a positive and positive effect on repeat intention. In addition, customer satisfaction has a positive effect on repurchase intention and plays a mediating role between service quality and repurchase intention. The implications of this study suggest that Putri Ayu Weaving should prioritise good service by providing staff training on operations, information accuracy, professionalism, and problem solving to meet customer needs and satisfaction. This study promotes a better understanding of consumer behaviour and provides better insights for businesses in the weaving industry. Originality – indicators measuring customer satisfaction act as a mediator between product quality and service quality on repurchase intention .